Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. The actuality of qualitative research and its challenges at Al-Quds University, as perceived  by a representative sample of university professors and student researchersCo-Prof. Mohammad Awad Shuibat, Mrs. Natasha Omar Abu Ziyad, Mr. Nayef Abd Alraouf Alkhateeb2. Employing secondary schools leaders for information and communications technology  and its effect on organizational culture in Al-MedinaMrs. Omneyah Abdullah Abutarboush3. Education and economic growth in Kingdom of Saudi Arabia during the period from 2000AD to 2020 ADMrs. Wafaa Mohamad Al-Otaibi4. The role of the Palestinian Ministry of Education in influencing Palestinian students' attitudes toward vocational and technical education from experts’ perspectiveMr. Amjad Ziad Hassan Sheikh Ali5. The effectiveness of an enrichment teaching program based on STEM approach in developing the 21st skills of intermediates school studentsDr. Nasser Mohammed Almutairi6. Mindfulness and its relationship to the quality of academic life in the light of distance education on a sample of master's students at Taif UniversityMrs. Esraa Saad Alomari, Dr. Azza Mohammed Abdu Hella
Keywords: Journal of Educational and Psychological Sciences